Analisis Perilaku Deteksi Dini Kanker Serviks pada Paramedis di Puskesmas Cibitung - Faulina, Riza; Hidayah, Sri Jadiansyah Suryanah (Universitas Malahayati, 2025)
ABSTRACT Cervical cancer is a disease that can be prevented by screening. Screening is an examination carried out on a healthy population, to differentiate people who are sick or at risk of developing a disease among healthy people (Minister of Health, 2015). This study aims to determine the behavior of early detection of cervical cancer among paramedics at the Cibitung Community Health Center. This research uses a cross sectional study design. The sampling technique uses purposive sampling. The instrument in this research uses a questionnaire that has been tested for validity and reliability. Data analysis using Chi-Square. Research results show the influence of husband's knowledge and support in carrying out early detection of cervical cancer for paramedics at the Cibitung Community Health Center in 2024. Husband's support has the highest OR value, namely 22.66. There is no relationship between length of work and early detection behavior of cervical cancer among paramedics at the Cibitung Community Health Center in 2024. Of the 30 paramedics, it was found that 88.1% had worked for > 5 years, 61.5% had good knowledge, 52.4% had negative perceptions, 64.3% had no personal risk factors, and 60.1% lacked husband support. %. It is hoped that paramedics will involve husbands more in carrying out early detection of cervical cancer. Keywords: Early Detection of Cervical Cancer, Paramedic, Length of Work, Knowledge, Husband's Support. ABSTRAK Kanker serviks adalah penyakit yang bisa dicegah dengan melakukan skrining. Skrining merupakan pemeriksaan yang dilaksanakan pada populasi masyarakat yang sehat, untuk memberdakan masyarakat yang sakut atau berisiko terkena suatu penyakit di antara masyarakat yang sehat (Menkes, 2015). Penelitian ini bertujuan untuk mengetahui bagaimana perilaku deteksi dini kanker serviks pada paramedis di Puskesmas Cibitung. Penelitian ini menggunakan rancangan desain studi cross sectional. Tekhnik pengambilan sampel menggunakan purposive sampling. Instrumen dalam penelitian ini menggunakan kuesioner yang sudah dilakukan uji validitas dan reliabilitas. Analisis data menggunakan Chi-Square. Hasil penelitian Terdapat pengaruh pengetahuan, dan dukungan suami dalam melakukan deteksi dini kanker serviks terhadap paramedis di Puskesmas Cibitung tahun 2024 . Dukungan suami memiliki nilai OR tertinggi yaitu 22,66. Tidak ada hubungan lama bekerja terhadap perilaku deteksi dini kanker serviks pada paramedis di Puskesmas Cibitung tahun 2024. Dari 30 paramedis didapatkan lama bekerja > 5 tahun 88,1%, memiliki pengetahuan baik 61,5%, persepsi negatif 52,4%, tidak memiliki faktor risiko diri 64,3%, dan dukungan suami kurang 60,1%. Diharapkan kepada paramedis agar lebih melibatkan suami dalam melakukan deteksi dini kanker serviks. Kata Kunci: Deteksi Dini Kanker Serviks, Paramedis, Lama Bekerja Pengetahuan, Dukungan Suami.